Modernisasi Pendidikan Islam di Mesir dalam Pemikiran Rifa’ah Rafi’ Al-Tahtawi - Manggala, Kayan; Aniqotul ‘Athiyyah, Avita; Kholil, Ahmad (CV. Kalimasada Group, 2024)
This research was conducted with the aim of describing a figure named Rifa'ah Rafi al-Tahtawi who is known as a modernizer of Islamic education in Egypt. This research method uses descriptive narrative research by describing the figure of a Rifa'ah Rafi al-Tahtawi in the Islamic world, how his reforms, contributions, and the fruits of his thoughts. The data sources that researchers use and become reference materials are the main book by Hana Fakhury, Tarikh al-adab al-Araby al-adab al-Hadith and several other reference books such as; Rifa'ah a-Tahtawi; The Islamic Education Reformer by M. Fazlurrahman Hadi, Lc, M.Pd.I. The results of this study are the biographical presentation of Rifa'ah Rafi' al-Tahtawi, Rifa'ah al-Tahtawi's works, and Rifa'ah al-Tahtawi's thinking in modernizing education in Egypt which includes; Universalization and Generalization of Education for All Muslims, Urgency of Education for Women, Existence of Enlightenment and Renewal Thought of Rifa'ah Rafi' al-Tahtawi, and Reconciling Arab-Islamic Tradition and Western Tradition.